Need for improved public health protection of young people wanting body piercing: evidence from a look-back exercise at a piercing and tattooing premises with poor hygiene practices, Wales (UK) 2015. Issue 9 (30th April 2018) - Perry, M.; Lewis, H.; Thomas, D. Rh.; Mason, B.; Richardson, G.
Abstract: Following a cluster of serious pseudomonas skin infections linked to a body piercing and tattooing premises, a look-back exercise was carried out to offer clients a screen for blood-borne viruses. Of those attending for screening 72% (581/809) had a piercing procedure in the premises of interest: 94 (16%) were under 16 years of age at the time of screening. The most common site of piercing was ear (34%), followed by nose (27%), nipple (21%) and navel (21%). A small number (<5) tested positive for hepatitis B and C, with no evidence this was linked to the premises. However, 36% (211/581) of clients reported a skin infection associated with their piercing. Using data from client forms, 36% provided a false age. Those aged under 16 years (OR 4.5, 95% CI 2.7–7.7) and those receiving a piercing at an intimate site (OR 2.1, 95% CI 1.3–3.6) were more likely to provide a false age. The findings from this exercise were used to support the drafting of the Public Health (Wales) Bill which proposed better regulation of piercing premises and the need to provide proof of being 18 years of age or over before having a piercing of an intimate site.